Early growth evaluation and estimation of heritability in a sengon (Falcataria moluccana) progeny testing at Kediri, East Java, Indonesia - aditya nugroho; DEDEN D. MATRA; ISKANDAR Z. SIREGAR; NOOR F. HANEDA; YUNIK ISTIKORINI; RIKA RAHMAWATI; YAHYA AMIN; ULFAH J. SIREGAR (Society for Indonesian Biodiversity, 2021)
Abstract. Nugroho A, Matra DD, Siregar IZ, Haneda NF, Istikorini Y, Rahmawati R, Amin Y, Siregar UJ. 2021. Early growth evaluation and estimation of heritability in a sengon (Falcataria moluccana) progeny testing at Kediri, East Java, Indonesia. Biodiversitas 22: 2728-2736. Sengon (Falcataria moluccana) is widely cultivated as a monoculture plantation in community forests that still poses a high risk of pest and disease attacks. Although plants naturally show signs of resistance, there is still however a lack of understanding on the influence of relative plant resistance on growth due to environmental and genetic factors. This study was aimed to evaluate the early growth of a sengon progeny testing in Kediri, East Java and to estimate the genetic parameters with respect to its resistance and susceptibility to stem borer and rust disease. Progeny test was designed using randomized complete block design (RCBD) with four blocks as replications. Each block consists of 100 families which was grouped into two categories, 50 families for resistant group and 50 families for susceptible group. Observations were made at the age of 0 and 9 months after planting on 9 individuals per plot in each family. Growth characteristics were measured as germination (%), height (m), and diameter (cm). Results indicated that the sengon growth rate from resistant and susceptible plant groups showed a significant difference. Heritability values are classified as moderate, ranging between 0.107 to 0.133 and 0.102 to 0.150 for height and diameter variables, respectively. These information may be used for gradual selection by considering the appropriate intensity.